Left Hepatectomy for Hepatocellular Carcinoma left liver with underlying cirrhosis and portal hypertension - Kaushal Yadav (Archives of Clinical Gastroenterology - Peertechz Publications, 2018)
Introduction: Hepatocellular carcinoma (HCC) is a major public health problem worldwide and is the second most common cause of cancer related deaths worldwide. If liver functional reserves and future liver remnant are adequate than liver resection is preferred choice in Child Pugh class A and selected cases of early Child Pugh class B, while Child Pugh B and C are candidates for liver transplantation. Case Presentation: The present case describes technical details of left lobectomy with underlying cirrhosis and mild portal hypertension.  Discussion: Case described in this report provide guidance that liver resection is the optimal treatment strategy for localized hepatocellular carcinoma in background of child Pugh A cirrhosis.  Conclusion: Liver resection is the treatment of choice for localized liver cancer in suitable patients if the future liver remnant is adequate and liver functions are within acceptable range. Clinical assessment, liver function evaluation, radiological interpretation, sound surgical skills and good perioperative care are the key for a successful outcome after surgical treatment for liver resection.